Engineering 2.0: an approach to support cross-functional teams in overcoming knowledge-sharing barriers in PSS design. (1st January 2011) - Bertoni, Marco; Larsson, Andreas
The paper discusses the key enabling mechanisms introduced by Web 2.0 technologies that can support Product Service Systems (PSSs) development teams in increasing the quality of early design decisions. The paper collects success stories and lessons learned from two empirical case studies in the aeronautical supply chain, and from a set of questionnaires forwarded to major automotive manufacturers, about the implementation of Engineering 2.0 tools, such as wikis, blogs and forums, to overcome knowledge-sharing barriers between cross-functional design teams. The study reveals that bottom-up and lightweight technologies can enable the implementation of more value-driven development processes, providing means for locating expertise in the extended organisation, for capturing the 'context' of the information managed, and for assessing and validating knowledge assets in a more collaborative fashion. Eventually, it points to the most relevant issues that currently prevent the implementation of Web 2.0 technologies in a product development setting.